PERBEDAAN MOTIVASI BELAJAR MATEMATIKA DALAM MENINGKATKAN MINAT BELAJAR SISWA LAKI-LAKI DAN PEREMPUAN - Feggy Pratami Suherman; Dewi Asiyah (Jurnal Eksplorasi Bimbingan dan Konseling, 2019)
The average score of mathematics subjects from 64 grade VIII students of 54 is stated to be less than the KKM (Minimum Graduation Criteria) that has been determined that is 70. The teacher explains some of the causes of low motivation and interest in student learning because students lack understanding on the previous material.This study uses quantitative descriptive research, where researchers use descriptive methods with a quantitative approach. the population is all eighth grade students at Mekarwangi Lembang Middle School 2016/2017 school year. The number of students is 64 students.